Pemanfaatan Beberapa Jenis Tanaman Berpotensi Pestisida untuk Mengendalikan Hama Kutu Putih pada Bibit Sengon (Falcataria mollucana) - Karti Rahayu Kusumaningsih; Agus Prijono; Hastanto Bowo Woesono; Mentari Kelana Devi (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2023)
One problem of cultivation of Falcataria mollucana seedlings in nursery is attack of Pseudococcus calceolariae pest. Attack of that pests cause the growth of seedlings hampered and finally cause death seedlings. Several plants founded in the field, for examples Swietenia macrophylla, Azadirachta indica, Morinda citrifolia and Carica papaya have bioactive compounds that can be used as botanical pesticide. The purpose of this research is to know type of leaf extract against effectivity of P. calceolariae pest control to F. mollucana seedlings based on decrease of incidence and severity against P. calceolariae attack. Results of the research showed that leaf extract of S. macrophylla, A. indica, M. citrifolia and C. papaya were effective to control P. calceolariae pest at F. mollucana seedlings. A. indica leaf extract gived decrease of incidence and severity against P. calceolariae attack higher than others leaf extract. i.e 80,13% and 57,69%.